Hans J. Teuteberg (editor): European Food History, a Research Review - M, V. R. (Petits Propos Culinaires, 1993)
Hans J. Teuteberg (editor): European Food History, a Research Review: Leicester University Press, Leicester and London, distributed in the USA and Canada by StMartin’s Press, 1992: 400 pp, £55.00.